Are All Measures of International Reserves Created Equal? An Empirical Comparison of International Reserve Ratios - Clement Yuk-pang Wong; Yin-Wong Cheung (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
Using available annual data of 174 economies since 1957, we examine the similarities and differences of seven international reserve ratios. While individual international reserve ratios display substantial variations across economies, they are associated with an economy?s characteristics including geographic location, income level, stage of development, degree of indebtedness, and exchange rate regime. The association pattern varies across time and type of international reserve ratios. Interestingly, there is only limited evidence that Asian and non-Asian economies have significantly different international reserve hoarding behavior. Our results suggest that the inference about whether an economy is hoarding too many or too few international reserves depends on the choice of international reserve ratio. Further, different international reserve ratios exhibit different persistence profiles, but the evidence of dependence on structural characteristics is rather weak.
Keywords: F40; F30; 330; International reserve ratios; structural characteristics; cross-economy analysis; Reservewährung; Sozialprodukt; Vergleich; Welt